The Perception of the Severity of Facial Asymmetry among Laypersons, General Practitioners, Orthodontists, and Maxillofacial Surgeons - Nazgol Zamanian; Alireza Jafari-Naeimi (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: The degree of asymmetry perception of dental and medical practitioners is influenced by several factors. The perceived asymmetry affect the treatment plan design. Purpose: The aim of the present study was to investigate the consistency of facial asymmetry and identify the amounts of transverse asymmetry that can be regarded as normal and might need correction. Materials and Method: In this cross-sectional descriptive study, three-dimensional (3D) images of a man and a women volunteer were obtained. Then transverse changes were applied by ZBrush software so that for each volunteer, seven 3D images of their face with varying degrees of facial transverse asymmetry were created. Then, the images were displayed to four groups of observers including layperson, general dentists, orthodontists, and maxillofacial surgeons. Finally, the consistency of the perception of these four groups of observers with the different degrees of facial asymmetry was compared. Results: Fourteen photographic samples were evaluated and ranked by 80 observers in four groups. The consistency of the perception of the facial transverse asymmetry was equal to 33%, which indicated a lack of consistency. Conclusion: According to the findings of this study, there was no consistency between the groups. The perception of dental professionals and ordinary people regarding the severity of transverse facial asymmetry seems to be inconsistent.